Functional Limb Salvage Following a 24-Hour-Delayed Fasciotomy for Pediatric Hand Compartment Syndrome: A Case Report - Rohman Sungkono; Adri Yandra Hidayat; Andrea Valentino; Ade Wirdayanto; Arip Heru Tripana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Acute compartment syndrome (ACS) in the pediatric hand is a formidable surgical emergency where delayed diagnosis can lead to devastating neuromuscular deficits and limb loss. The narrow therapeutic window, often termed the "golden hours," is considered critical for preventing irreversible ischemic necrosis. Presentations delayed beyond this period, especially in pre-verbal children, pose a significant clinical and ethical dilemma regarding the utility and risks of surgical intervention. Case presentation: A 2-year-old female presented to our emergency department 24 hours after a severe crush injury to her right hand from a noodle-making machine. The hand was massively swollen, cyanotic, and insensate, with no detectable capillary refill or digital oximetry readings. A clinical diagnosis of advanced, multi-compartmental ACS was made. Emergency surgical decompression was performed via seven incisions, releasing all ten osteofascial compartments. Intraoperative assessment revealed dusky, non-contractile but bleeding muscle. Following staged debridements, the patient demonstrated remarkable recovery. At six months, she achieved full range of motion in all digits except the middle finger and demonstrated age-appropriate grip and pincer grasp, with the primary sequela being a fixed flexion contracture of the middle finger's proximal interphalangeal joint. Conclusion: This report highlights a case of unexpected functional recovery following a significantly delayed fasciotomy. The outcome supports a nuanced approach to delayed pediatric ACS, suggesting that in select cases, aggressive surgical decompression should be considered as the potential for a positive outcome may exist. This case serves as a powerful, hypothesis-generating observation that raises critical questions about the absolute temporal limits for surgical intervention and underscores the importance of individualized surgical judgment.